Milking practices on commercial Holstein-Friesian farms - Ózsvári,László (2021)
ABSTRACT The objective of this study was to survey and analyze milking practices of commercial Holstein-Friesian farms. A total of 43 Hungarian dairy farms with 31,430 cows was surveyed by using a questionnaire via personal interviews. Furthermore, seven in-depth, individual interviews were conducted with farm managers. In the statistical analysis, we used ANOVA models. The results showed that 57.8% of the milking parlors had a herringbone design, followed by parallel (20.0%) and rotary (17.8%) milking systems. For the interviewed farm managers, gentle (71.4%) and quick milking (57.1%) as well as herd size (57.1%) were the most important factors in determining the milking system design. In 62.8% of the farms, cows were milked twice a day, and the average milking time was 5.0 h with an average of 3.1 laborers. The average daily milking time per cow was 15 min and the average daily walking time per cow to the milking parlor and back was 24 min. Furthermore, 85.4% of the farms used traditional elastic milk liners, whereas 14.6% used silicone ones. In total, 57.1% of the interviewed farm managers said that the ideal teat liner should fit the teats correctly and provide gentle milking. Prior to milking, 65.1% of the farms used disinfectant dip and 11.6% used a disinfectant wash, whereas 23.3% still washed the udder with water. The udder was wiped with paper towels in 73.8% of the herds and with cloth in 26.2% of the herds. Forestripping was performed in all herds: 51.2% onto the floor, 46.5% into a cup, and in 2.3% into a paper towel. Further, 85.7% of the interviewed farm managers considered the use of a cup to be the ideal method, but 57.1% deemed a dark-colored piece of rubber/flooring to be similarly acceptable. Cows with mastitis were milked separately in 91.9% of the farms.